A Physician’s Perspective on Volunteering Overseas… It Is Not All about Sharing the Latest Technology - Kolkin, Jon (Frontiers in Surgery, 2018)
As healthcare professionals, there often comes a time in our career when we are intrigued by the possibility of participating in humanitarian work in underserved countries. However, the desire to serve is often tempered by some ambivalence about whether our skill sets are applicable in less technologically advanced healthcare settings. Furthermore, there may be some concern about the cultural and logistical challenges one might face while working overseas. A volunteer may also be worried that, despite their best intentions, the medical personnel in the host country will not take advantage of our knowledge and their patients will not achieve the best results. As a consequence, a talented and well-intentioned professional may decide not to volunteer, resulting in a lost opportunity to participate in what can be an extremely rewarding experience. I will be discussing a number of key factors that can strongly influence the quality of one’s experience from the perspective of a Hand Specialist. My comments will primarily be a reflection of my personal experience over 20 years as a member of Health Volunteers Overseas (www.hvousa.org).